2006
DOI: 10.1073/pnas.0602249103
|View full text |Cite
|
Sign up to set email alerts
|

The Dam1 kinetochore complex harnesses microtubule dynamics to produce force and movement

Abstract: Kinetochores remain attached to microtubule (MT) tips during mitosis even as the tips assemble and disassemble under their grip, allowing filament dynamics to produce force and move chromosomes. The specific proteins that mediate tip attachment are uncertain, and the mechanism of MT-dependent force production is unknown. Recent work suggests that the Dam1 complex, an essential component of kinetochores in yeast, may contribute directly to kinetochore-MT attachment and force production, perhaps by forming a sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
215
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(230 citation statements)
references
References 42 publications
10
215
2
Order By: Relevance
“…This persistent tip tracking has enabled us to measure the effects of continuous tension on MT dynamic parameters in a reconstituted system for the first time. In our assay, beads coated with the Dam1 complex are attached to the tips of individual dynamic MTs grown from stabilized seeds anchored to a glass coverslip 14,22, 23 (Fig. 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This persistent tip tracking has enabled us to measure the effects of continuous tension on MT dynamic parameters in a reconstituted system for the first time. In our assay, beads coated with the Dam1 complex are attached to the tips of individual dynamic MTs grown from stabilized seeds anchored to a glass coverslip 14,22, 23 (Fig. 1a).…”
mentioning
confidence: 99%
“…To overcome these limitations, we relied on a motility assay using the Dam1 complex 11 (also known as DASH, or DDD), a putative load-bearing component of kinetochores in yeast [11][12][13][14]26 . Like kinetochores, pure recombinant Dam1 complex forms robust connections to growing and shortening MT tips that remain attached even when tension is applied 14 .…”
mentioning
confidence: 99%
“…It can bind to depolymerizing microtubule ends (13) and stay attached to the end of polymerizing or depolymerizing microtubules even against a force of up to 3 pN (12). The level of force is similar to that generated by ATP-driven motors that move organelles inside cells.…”
Section: The Dam1 Complex: Rings Around Microtubulesmentioning
confidence: 96%
“…Rings are difficult to detect in vitro in the absence of microtubules suggesting that microtubules might guide the assembly of these structures. The lack of 1:1 stoichiometry between the number of Dam1 complexes and the number of protofilaments argues that Dam1 does not bind tightly to one part of the tubulin dimer and thus could have a loose grip that allows free movement along the microtubule (12). Recent results suggest that flexible tethers on two of the proteins (Dam1 and Duo1) bind to the microtubule (11).…”
Section: The Dam1 Complex: Rings Around Microtubulesmentioning
confidence: 99%
“…However, while such rings may efficiently couple microtubule depolymerization to chromosome movement in a system where kinetochores bind only to a single microtubule [130,131], they are not essential in fission yeast [132] and orthologues have never been found outside fungi. Additionally, it was subsequently shown that ring formation is not required for microtubule depolymerization-driven motion of the Dam1 complex [133,134].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%